Effects of Oxygenated Acids on Graphene Oxide: The Source of Oxygen-Containing Functional Group - Zhu, Xinghua; Xu, Yuanpu; Lu, Zhibin; Xue, Qunji (Frontiers in Chemistry, 2021)
Graphene oxide is an important member of the graphene family which has a wide range of applications. The chemical method, especially the liquid phase method, is one of the most common and important methods for its preparation. However, the complex solution environment not only gives them rich structure, but also brings great challenges for its large-scale industrial synthesis. In order to better realize its industrial application, it is important to understand its structure, such as the source of oxygen-containing functional groups. Here we studied the contribution of four oxygenated acids to oxygen-containing functional groups in Hummers' method using first principles. We found that the permanganic acid molecules that exist instantaneously due to energy fluctuations can be the source of oxygen-containing functional group. In addition, Stone-Wales defect have a certain effect on the formation of oxygen-containing functional groups, but this effect is not as good as that of solvation effect. This work provides a guide for exploring the source of oxygen-containing functional groups on graphene oxide.